PENGEMBANGAN SUMBER DAYA MANUSIA IBU PKK SEBAGAI AGEN PEMBANGUNAN KELUARGA DI DESA BANTAR AGUNG, MAJALENGKA JAWA BARAT - Enny Diah Astuti; Umi Hanik Makmuroh; Verus Hardian; Niantoro Sutrisno; Adinda Azzahra (POLITEKNIK LP3I JAKARTA, 2026)
The family Welfare Movement (PKK) is an empowerment movement that strives for community economic independence. Family independence is key to village social resilience. The Bantar Agung Village family welfare movement (PKK) has great potential as agents of change, but the human resource capacity of cadres still needs to be improved. This community service activity aims to develop the human resources of PKK mothers through a four pillar program to encourage family independence: local potential,the strategic role of PKK mothers, the empowerment model, and success indicators. Obstacles in this community service activity are the double burden on women and cadre regeneration. A community of practice based human resource development model is recommended for program sustainability.